2021
DOI: 10.1038/s41598-021-94190-9
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive transferability evaluation of U-Net and ResU-Net for landslide detection from Sentinel-2 data (case study areas from Taiwan, China, and Japan)

Abstract: Earthquakes and heavy rainfalls are the two leading causes of landslides around the world. Since they often occur across large areas, landslide detection requires rapid and reliable automatic detection approaches. Currently, deep learning (DL) approaches, especially different convolutional neural network and fully convolutional network (FCN) algorithms, are reliably achieving cutting-edge accuracies in automatic landslide detection. However, these successful applications of various DL approaches have thus far … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(54 citation statements)
references
References 49 publications
3
51
0
Order By: Relevance
“…ResU-Net [67,68], as a classical network in semantic segmentation, has achieved great success in landslide detection tasks [34,38,39]. It has been demonstrated that the skip connection in U-Net effectively alleviates the detail loss problem due to convolution, and the residual structure prevents the vanishing gradient when mining deeper information [38].…”
Section: Attention Transu-netmentioning
confidence: 99%
See 1 more Smart Citation
“…ResU-Net [67,68], as a classical network in semantic segmentation, has achieved great success in landslide detection tasks [34,38,39]. It has been demonstrated that the skip connection in U-Net effectively alleviates the detail loss problem due to convolution, and the residual structure prevents the vanishing gradient when mining deeper information [38].…”
Section: Attention Transu-netmentioning
confidence: 99%
“…Furthermore, Qi et al [38] proved that the U-Net with ResNet50 can improve the performance of the model on rainfallinduced landslide detection. Ghorbanzadeh et al [39] firstly used the free Sentinel-2 data in landslide identification by evaluating the performance of U-Net and ResU-Net in three different landslide areas, the result indicated that ResU-Net obtained the highest F1-score. To alleviate the lack of generalization of the model caused by various landslide morphologies, Yi et al [18] introduced an attention mechanism to assign weights for important feature maps in ResU-Net, the F1-score on the proposed model was improved by 7% compared to ResU-Net.…”
Section: Introductionmentioning
confidence: 99%
“…We extracted patches of 128 x 128 pixels from the input satellite images, as suitable input for CNNs, based on Ghorbanzadeh et al (2021) and Prakash et al (2021), who reported optimal accuracies of F1score, Precision, and Recall using this patch size. By rasterizing the manual inventory of the different years with 5 meter grid cells, the associated binary masks were created.…”
Section: Study Areamentioning
confidence: 99%
“…The U-Net model has been used extensively for landslide detection (Ronneberger, et al, 2015) due to its robust network structure and segmented pixels as outputs (Ghorbanzadeh, et al , 2021;Prakash et al , 2021;Zhang et al, 2018). The U-Net model (Figure 3) has many advantages.…”
Section: Model Training and Transfer Learningmentioning
confidence: 99%
“…But these methods are lacking in accuracy and recognition speed. Some scholars use u-net neural network to extract landslide deformation information (Ghorbanzadeh et al, 2021). Sanghoon Lee et al, used U-Net to quantitative spatial analysis on whole slide images (Lee et al, 2020).…”
Section: Introductionmentioning
confidence: 99%